The impact of total quality management practices on export performance of apparel exporters of sri lanka - Abeykoon, M.W.B.; De Alwis, A.C. (University of Jaffna, 2016)
In today's global competition and economic liberalization, quality has become one of the important factors for achieving competitive advantage. And this ever-increasing demand for quality product and services had forced organizations to invest substantial resources in Total Quality Management (TQM) strategies. The present day international market environment is characterized by increased number of competitors and intensified efforts at all levels and each domain. Under these circumstances quality development and its continuous advancement has developed a significant meaning. Developed countries often resist exports from developing countries if the exports do not meet their country quality standards. And Sri Lanka like other developing economies is also trying hard to exploit business opportunities in international markets and has succeeded as far as textiles and apparel industry. Purpose of this study was to examine the impact of total quality management practices (TQMP) on export performance (EP) of apparel exporters of Sri Lanka. A five point Likert scale questionnaire was used as the key instrument of data collection and data were obtained from 65 apparel exporters of Sri Lanka. Eight dimensions were used to measure TQMP including Leadership, Training, Employee Management, Information and Analysis, Supplier Management, Process Management, Customer Focus and Continuous Improvement. The correlation and regression analysis were used to examine the impact of TQMP on EP and the relationship between TQMP and EP. Results of the study clearly indicated that all dimensions except Information and Analysis were significantly correlated with EP. In addition, customer focus, continuous improvement and supplier management were found as the most significant dimensions that impact on EP.
Keywords: Apparel exporters; Export performance; Total quality management practices